A review of surgical options for management of periprosthetic fractures in total hip arthroplasty. Issue 3 (May 2017) - Romero, Jose A.; Gates, Stephen; Huo, Michael
Abstract : The number of people living with a total hip arthroplasty continues to increase worldwide. Patients who have undergone total hip arthroplasty are living longer and have more active lifestyles. With increasing total hip arthroplasty utilization in more active patients the incidence of periprosthetic fracture is expected to rise. A variety of surgical techniques exist to manage various fracture patterns, and patient outcomes hinge on the success of each technique. This brief review summarizes some of the current evidence-based treatment options for periprosthetic fractures around a total hip arthroplasty.